DEGRADATION OF ACETATE, PROPIONATE, AND BUTYRATE UNDER SHOCK TEMPERATURE - OZTURK, M (ASCE-AMER SOC CIVIL ENGINEERS, 1993)
Experiments were performed to determine the degradation of acetate, propionate, and butyrate, and the maximum methanogenic activity of granular sludge from the thermophilic anaerobic digestion (55-degrees-C) of pure molasses under shock temperature conditions. The compositions of acetate, propionate, and butyrate that were used as substrates were 25:35:40, respectively. On two duplicate batch reactors (I and II) running in parallel and at a pH of 7, the tests were performed at 63-degrees-C during the first volatile fatty acid (VFA) addition (first feeding or first experiment) and at 55-degrees-C after the second VFA addition. During the first and second VFA additions, there was a lag phase. In the first experiment, by the end of 160 hours, after the initial concentrations of butyrate and acetate had been completely degraded, only 35-55% of the initial concentration of propionate was converted to acetate. The maximum methanogenic activities of the first feeding were not high because the population of propionate degrading bacteria was low and these bacteria were negatively affected from the shock temperature changes. In the second experiment, with the same sludge, the maximum methanogenic activities on second VFA additions were about 1.3 times higher than those of the first VFA additions. This increase may be due to a faster adaptation of the sludge and an increase of the population of the propionate degrading bacteria as a result of returning to the optimum temperature conditions.
Keywords: ANAEROBIC DEGRADATION; WASTE-WATER; DIGESTION; SUBSTRATE; REACTORS; ACIDS; Engineering; Environmental Sciences & Ecology